2012
DOI: 10.1177/1074248412455696
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide- and Heme-Independent Activation of Soluble Guanylate Cyclase Attenuates Peroxynitrite-Induced Endothelial Dysfunction in Rat Aorta

Abstract: Oxidative stress interferes with nitric oxide (NO)/soluble guanylate cyclase (sGC)/cyclic guanosine monophosphate (cGMP) signalling pathway through reduction of endogenous NO and formation of the strong intermediate oxidant peroxynitrite and leads to vascular dysfunction. We evaluated the effects of oral treatment with NO- and heme-independent sGC activator cinaciguat on peroxynitrite-induced vascular dysfunction in rat aorta. Sprague-Dawley rats were treated orally 2 times at an interval of 17 hours with vehi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 32 publications
1
19
0
1
Order By: Relevance
“…In fact, exposure to peroxynitrite decreased the relaxant potency and efficacy of either nitroglycerin or acidified NaNO 2 in endothelium-denuded rat iliac arteries. Similar effects of peroxynitrite on an NO donor-induced vasorelaxation have been reported by a number of investigators [8,18,19]. Since the impairment by peroxynitrite of NO-mediated relaxation in the present study was also observed in the presence of SOD or tempol, a causal mediator responsible for this seems to be peroxynitrite itself.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In fact, exposure to peroxynitrite decreased the relaxant potency and efficacy of either nitroglycerin or acidified NaNO 2 in endothelium-denuded rat iliac arteries. Similar effects of peroxynitrite on an NO donor-induced vasorelaxation have been reported by a number of investigators [8,18,19]. Since the impairment by peroxynitrite of NO-mediated relaxation in the present study was also observed in the presence of SOD or tempol, a causal mediator responsible for this seems to be peroxynitrite itself.…”
Section: Discussionsupporting
confidence: 67%
“…The heme iron of sGC is no exception either, because spectroelectrochemical analysis has demonstrated that peroxynitrite readily oxidizes the ferrous heme iron of sGC to the ferric state [17]. In this regard, an impaired and augmented effect of peroxynitrite on the relaxant response to an NO donor [8,18,19] and an sGC activator [8], respectively, has been reported. However, it is not entirely clear how peroxynitrite modulates the NO/sGC/cGMP pathway, especially the sGC redox equilibrium, in the vasculature.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, a number of intra-and intercellular targets for bioactive NO have been identified with the biological effects ranging from enzyme activation or inhibition, posttranslational modifications altering protein function, including S-nitrosylation and tyrosine nitrosation, and the generation of complex reactive nitrogen and oxygen species through the rapid spontaneous reaction of NO with other gaseous molecules in the cell (Ignarro, 1991;Davidge et al, 1995;Xu et al, 1998;Handy and Loscalzo, 2006;Yoshida et al, 2006;Kang-Decker et al, 2007;Selemidis et al, 2007;Zuckerbraun et al, 2007;Illi et al, 2008;Briones et al, 2009;Fernhoff et al, 2009;Lima et al, 2010;Thibeault et al, 2010;Bess et al, 2011;Choi et al, 2011;Straub et al, 2011;Marin et al, 2012;Haldar and Stamler, 2013;Korkmaz et al, 2013).…”
Section: A a Case For Endothelial Nitric-oxide Synthase And Nitric Omentioning
confidence: 99%
“…Irodalmi adatok szerint az sGC aktivátor cinaciguat (BAY 58-2667) az sGC NO-ra érzéketlen formájának hemkötő zsebéhez kapcsolódik, így helyreállítja annak cGMP-termelését (15). Újabb tanulmányok a cinaciguat jótékony hatását bizonyították miokardiális infarktus (16), miokardiális iszkémiás-reperfúziós károsodás modelljeiben (17, 18), nitro-oxidatív stressz által indukált endothelialis diszfunkcióban (19), vaszkuláris neointima-képződés esetén (20) és a patológiás szívizom-hipertrófi a megelő-zésében (21). A cinaciguat biztonságosságát és tolerálhatóságát humán klinikai vizsgálatokban (fázis I.)…”
Section: Bevezetésunclassified